Farm size and agricultural productivity of nutritious foods: Evidence from Ethiopia - Ameye, Hannah; Bachewe, Fantu Nisrane; Minten, Bart; Tamru, Seneshaw (Wiley, 2025)
Agri-food systems are transforming quickly in Africa. An important issue in the transformation process of agricultural production is the role of small farms. While many authors have looked at this question, one aspect that has received little attention is the role of small farms in the production of nutritious foods, an important topic given the low availability and relatively high prices of nutritious foods and the consequent low level of nutrition security in the continent. Using a unique large-scale dataset from Ethiopia—one of the largest countries in Africa that has been transforming rapidly—we look at the production of vegetables and dairy products. We find a strong association between farm size and partial productivity measured in terms of output, value of outputs and profit per hectare/cow, with productivity twice to four times as high for larger farms. These farms have substantially higher input expenditures as well as differences in farm technologies compared to small ones. Our findings have important implications for the debate on the role of small farms and nutritional improvements in the continent.